Pengembangan Perangkat Pembelajaran Fisika SMA Berbasis Pendekatan Induktif Guided Discovery Materi Gelombang Terintegrasi Bencana Tsunami - Naspin, Desi Ariyanti; Deswita, Pipi; Fauzi, Ahmad; Wulan, Ratna (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
The role of this research to be form a student disaster preparedness even earlier. This caused by Padang City is an area that is potentially tsunami to disasters. One of the approximation is integrate the material into tsunami disaster physics learning in high school. This role of research is to developt the physics learning tools by using Inductive and Guided Discovery approach in the matter of wave integrated disaster of tsunami. This type of research is the development of research. Model is a model used 4-D that consist of definition, design, development, and disseminate stage. This research show that high school physiscs learning tool by using Inductive and Guided Discovery approach in the wave matter and integrated tsunami disaster very valid, very practice and effective so it can be implemented on the learning process.